ФУНКЦІЇ ЛЕКСИЧНИХ ОДИНИЦЬ У СЕМАНТИЧНОМУ ПРОСТОРІ ХУДОЖНЬОГО ТЕКСТУ (НА МАТЕРІАЛІ РОМАНІВ ДЖОНА МАКСВЕЛЛА КУТЗЕЕ) - Holovashchenko, Yuliia (Видавничий дім «Гельветика», 2021)
The article is dedicated to the issue of functions of lexical units in a literary text. A literary text appeals with unique combination of content and sense, which is hidden beneath the linguistic surface and is subjected to interpretation. The most effective and interpretatively significant is the lexical level, i.e. the level of words whose meanings, while submerged in the linguistic environment of the text, acquire some new semantic value in relation to the content of the literary text. In this article lexical units are regarded as constituents of lexical structure that lays a foundation of formation of the semantic space of a literary text, i.e. the space of its meaning. Construction of the lexical structure of semantic space of a literary text is possible through selection of lexical units that correlate with generic peculiarities of the text.
FUNCTIONS OF LEXICAL UNITS IN SEMANTIC SPACE OF LITERARY TEXT (BASED ON NOVELS BY JOHN MAXWELL COETZEE)
Keywords: Literary text; Lexical unit; Semantic space; Function